Effect of dexmedetomidine on intracranial pressures during laparoscopic surgery: A randomized, placebo-controlled trial - Nishant Sahay; Umesh K Bhadani; Subhajit Guha; Alok Himanshu; Chandni Sinha; Mamta Bara; Anubha Sahay; Alok Ranjan; Prashant Singh (Wolters Kluwer Medknow Publications, 2018)
Background and Aims: Laparoscopic surgeries cause an increase in intracranial pressure (ICP) after creation of pneumoperitoneum. Sonographically measured, optic nerve sheath diameter (ONSD) correlates well with changes in ICP. Dexmedetomidine (Dex), an α2 agonist is extensively used in day-care surgeries, although its effect on ICP during laparoscopy in humans has not been reported in the literature. The aim of this study was to note the effect of dexmedetomidine infusion on changes in ICPs during laparoscopic cholecystectomy. Material and Methods: This was a prospective, randomized, placebo-controlled, double-blind study done on 60 patients scheduled for laparoscopic cholecystectomy. The study drug, dexmedetomidine hydrochloride (Dex) or placebo saline infusion, was started 10 min before induction and continued till extubation. Changes in ICP were assessed sonographically at baseline before pneumoperitoneum, 5 min after establishing pneumoperitoneum, 10 min after positioning the patient 20° head up, and 5 min after desufflation. Results: Demographically, both groups were comparable. The ONSD showed a significant increase after pneumoperitoneum in both groups (P = 0.0001 and 0.0011). Dex group could marginally attenuate this increase (P = 0.075). After changing patient's position to reverse Trendelenburg, ONSD increased further in both groups. Dex group could significantly attenuate the increase (P = 0.001). The ONSD did not return to baseline values till after 5 min of release of pneumoperitoneum in both groups. Conclusion: Dexmedetomidine is effective in attenuating increase in ICP associated with laparoscopic surgeries. The benefit was marked 10 min after placing patient in the reverse Trendelenburg position during laparoscopic cholecystectomy.